Fe/Co redox and surficial hydroxyl potentiation in the FeCo2O4 enhanced Co3O4/persulfate process for TC degradation. (1st July 2022) - Zhu, Tong; Jiang, Jinping; Wang, Jisheng; Zhang, Zhening; Zhang, Jiao; Chang, Jing
Abstract: A magnetic FeCo2 O4 /Co3 O4 nanocomposite was successfully synthesized by a facile hydrothermal method as an efficient activator for persulfate (PS) activation to degrade tetracycline (TC) in an aqueous solution. TC removal and mineralization efficiencies reached up to 91.63% and 43.57% in 120 min in the FCC-3/PS system, respectively. The mixed-valence of Fe/Co in the nanocomposite catalyst was beneficial for electrons transfer between Co and Fe elements and enhanced the redox circulation of Fe and Co in between divalent and trivalent. Surficial analysis and phosphate adsorption test confirmed the existence of –OH groups on the surfaces of FeCo2 O4 /Co3 O4 nanocomposite. Fe/Co redox and surficial hydroxyl in the catalyst played significant roles in the TC potentiation degradation, which was contributed by the plenty of adsorbed –OH groups and excellent dispersity of FeCo2 O4 in the FeCo2 O4 /Co3 O4 composite. The sulfate radicals were major species followed by the hydroxyl radicals, and the surficial adsorbed hydroxyl made great contributions to radical generation. The cycling test and intermediate toxicity analysis indicated that the nanocomposite was considered stable and practicable in water treatment. This work demonstrated that the FeCo2 O4 /Co3 O4 nanocomposite was an effective and environ-friendly catalyst towards PS activation for removing organic pollutants from water. Graphical abstract: Image 1 Highlights: Existence of Fe accelerated Fe/Co redox cycling in heterogeneous interfaces. Surficial hydroxyl improved PS activation ability by ≡Co(II)–OH formation. Sulfate and hydroxyl radicals were major species in PS activation by FeCo2 O4 /Co3 O4 . FeCo2 O4 /Co3 O4 /PS system was an effective and environ-friendly method for TC removing.